Financial media, price discovery, and merger arbitrage - Matthias M. M. Buehlmaier; Josef Zechner (Goethe University Frankfurt, Center for Financial Studies (CFS), 2016)
Using merger announcements and applying methods from computational linguistics we find strong evidence that stock prices underreact to information in financial media. A one standard deviation increase in the media-implied probability of merger completion increases the subsequent 12-day return of a long-short merger strategy by 1.2 percentage points. Filtering out the 28% of announced deals with the lowest media-implied completion probability increases the annualized alpha from merger arbitrage by 9.3 percentage points. Our results are particularly pronounced when high-yield spreads are large and on days when only few merger deals are announced. We also document that financial media information is orthogonal to announcement day returns.
urn:nbn:de:hebis:30:3-418707
Keywords: G11; G14; G34; 330; financial media; merger arbitrage; hedge funds; market efficiency; mergers and acquisitions